Doherty's Dominance Continued: A Linear PA Using GaN-on-Si - Deublein, Alexander; Loose, Michael; Illmer, Andreas; Musolff, Christian; Irnstorfer, Florian; Weigel, Robert; Ackermann, Thomas (IEEE Microwave Magazine, 2023)
Most RF and millimeter-wave systems for communications and radar include at least one transmitter used to up-convert, amplify, and potentially radiate the desired signal without distortion. Moreover, this part of the system, and in particular its power amplifier (PA), does typically dominate the total power consumption of electronic infrastructure systems. Thus, increasing the PA’s efficiency is the most effective way to enhance the overall power efficiency of such system
Keywords: Power Amplifier; PA; GaN; GaN-on-Si